2012
DOI: 10.1016/j.ygyno.2011.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor-infiltrating T cells in ovarian cancer: A meta-analysis

Abstract: Objective The presence of T cells within the epithelial component of tumors, as histologic evidence of anti-tumor immunity, has been associated with a survival advantage in multiple studies across diverse patient cohorts. We performed a meta-analysis of studies evaluating the prognostic value of tumor-infiltrating lymphocytes (TIL) on survival among women with ovarian cancer and to investigate factors associated with variations in this effect, including patient characteristics, surgical outcomes, tumor histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
440
3
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(476 citation statements)
references
References 35 publications
22
440
3
11
Order By: Relevance
“…In fact, tumor-infiltrating CD8 + T cells have been detected in subsets of patients with various cancers such as melanoma and carcinomas of the head and neck, breast, lung, prostate, bladder, kidney, colon, ovary, and esophagus [3]. Importantly, this T cell-inflamed phenotype correlates with positive treatment outcomes in these cancers and has been proposed as a prognostic biomarker [3][4][5][6][7][8][9][10]. For instance, the CD8 + T cell content in the core and invasive margin of colorectal tumors, a parameter termed "immunoscore", has been reported to be a better predictor of post-surgery disease-free and overall survival than the standard TNM staging [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, tumor-infiltrating CD8 + T cells have been detected in subsets of patients with various cancers such as melanoma and carcinomas of the head and neck, breast, lung, prostate, bladder, kidney, colon, ovary, and esophagus [3]. Importantly, this T cell-inflamed phenotype correlates with positive treatment outcomes in these cancers and has been proposed as a prognostic biomarker [3][4][5][6][7][8][9][10]. For instance, the CD8 + T cell content in the core and invasive margin of colorectal tumors, a parameter termed "immunoscore", has been reported to be a better predictor of post-surgery disease-free and overall survival than the standard TNM staging [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Median progressionfree survival (PFS) and median OS were 22.4 months and 50.3 months, respectively, for patients whose tumors contained TILs versus 5.8 months and 18.0 months for those whose tumors did not contain TILs (p<0.001 for both). The meta-analysis of 10 studies, including 1,815 patients with EOC, confirmed that lack of intraepithelial TILs correlated with worse OS (pooled HR=2.24, 95% CI=1.71-2.91) (29).…”
Section: Epithelial Ovarian Cancermentioning
confidence: 68%
“…The number and type of TILs influence the clinical outcome of patients with epithelial ovarian cancer (EOC) (28)(29)(30)(31)(32)(33). For instance, in the study of Zhang et al (28), the presence of TILs was detected in 54.8% of 186 frozen specimens from women with this malignancy and found to be correlated with increased expression of IFN-γ, IL-2 and lymphocyteattracting chemokines within the tumor.…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%
“…5 Correlation between the presence of TILs and prolonged progression-free (PFS) and overall (OS) survival has been demonstrated in patients with advanced stage ovarian carcinoma, 4,6 and the prognostic value of TILs was demonstrated to persist among all populations regardless of stage or grade of disease. 7 Specifically, the presence of CD8+ TILs has been demonstrated to correlate with increased survival. [6][7][8][9] Confirmed by systematic review, CD8+ TILs are a superior marker for prognosis, as their presence Ovarian cancer is the most deadly gynecologic malignancy, with more than 15,000 deaths anticipated in 2012.…”
Section: Immunotherapy In Ovarian Cancermentioning
confidence: 99%
“…7 Specifically, the presence of CD8+ TILs has been demonstrated to correlate with increased survival. [6][7][8][9] Confirmed by systematic review, CD8+ TILs are a superior marker for prognosis, as their presence Ovarian cancer is the most deadly gynecologic malignancy, with more than 15,000 deaths anticipated in 2012. 1 While approximately 80% of patients will respond to frontline chemotherapy, more than 60% of patients will experience disease recurrence and only 44% will be alive at 5 y.…”
Section: Immunotherapy In Ovarian Cancermentioning
confidence: 99%